Implementation of the 1995 Middle East Resolution: A Vital Lifeline to the Extension and Success of the Non-Proliferation Treaty - Haidy Y. Ghoname; Howard Lewis Hall (International Journal of Nuclear Security, 2016)
This study highlights the core non-proliferation dilemmas we face and suggests an effective mechanism for reviving the spirit and the hope of the Non-Proliferation Treaty. An indispensable key to the treaty calls for a rethinking of what we believe should be referred to as its four pillars: disarmament, non-proliferation, peaceful uses of nuclear energy, and implementation of the 1995 Middle East Resolution. We seek to contribute to the renaissance of the non-proliferation regime by addressing seven dilemmas that arise from the way various Non-Proliferation Treaty participants pursue the goals of the four pillars undergirding the treaty. This study highlights core problems which we believe may bring about—sooner or later—dissolution of the treaty. That treaty may then come to be replaced with another, more balanced, comprehensive, and fair treaty.
Keywords: ME/Middle East; NPT/Non-Proliferation Treaty; MENWFZ/ Middle East Nuclear Weapons Free Zone; NWS/Nuclear-Weapon States; NNWS/ Non-Nuclear-Weapons States; U.S/ The United States; IAEA/ International Atomic Energy Agency; UNSC/ United Nations Security Council; UNSG/ United Nations Security General; LAS/League of Arab States; AF/African Union; NAM/Non-Aligned Movement